2010
DOI: 10.1097/ico.0b013e3181cf98e5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Corneal Thickness Measurements Using Galilei, HR Pentacam, and Ultrasound

Abstract: Although differences between the devices were statistically significant, there was good correlation and agreement between Galilei and Pentacam in measuring central and thinnest corneal thickness. The corneal thickness measurements made with the HR Pentacam and Galilei also showed good correlation and agreement with those made with ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 31 publications
5
13
0
Order By: Relevance
“…In accordance with our data, previous studies also found that the Pentacam system underestimated the CCT value as compared to the Galilei system [14], and the Sirius system provided slightly higher TCT measurements compared to that obtained from the Pentacam system [18]. Different results, however, have been reported by other studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with our data, previous studies also found that the Pentacam system underestimated the CCT value as compared to the Galilei system [14], and the Sirius system provided slightly higher TCT measurements compared to that obtained from the Pentacam system [18]. Different results, however, have been reported by other studies.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have compared CCT and/or thinnest corneal thickness (TCT) measurements obtained by some of these instruments, such as between a single rotating Scheimpflug camera, the Pentacam (Oculus, Wetzlar, Germany) and a single rotating Scheimpflug camera combined with a Placido disc corneal topographer, the Sirius (Costruzione Strumenti Oftalmici, Florence, Italy) [18], [19]; between the Pentacam and a dual Scheimpflug camera combined with a Placido disc corneal topographer, the Galilei (Ziemer, Port, Switzerland) [14]; and between the Pentacam and the RTVue-100 FD-OCT (Optovue Inc., Freemont, CA, USA) [13], [20][22]. Other studies have assessed the agreement between MPCT measurements [9], [22].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to recent GSA studies in normal subjects, CCT values in this study were similar. A mean value of 549.2±30.5 µm for 77 normal eyes was reported by Zaina, which is thicker than the 541.27±30.07 µm for 92 eyes in a study by Ladi et al, but thinner than the 560.57±29.10 µm reported for 47 eyes by Hosseini et al [18][20] A number of factors may affect CCT, such as age, race, gender, refractive error, and corneal curvature. [8][10] In our study, we found that CCT decreased approximately 3.2 µm for each decade of increase in age.…”
Section: Discussionmentioning
confidence: 76%
“…Corneal thickness is considered an important indicator of corneal health, and it can be evaluated through the use of several methods, including ultrasonic pachymetry, optical slit-lamp pachymetry, confocal microscopy, specular microscopy, and partial coherence interferometry. Several reports have found corneal thickness measurements performed by the Pentacam and its pachymetric map to be reliable and reproducible [5,[23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%